Topologically tunable local-resonant origami metamaterials for wave transmission and impact mitigation. (31st March 2023) - Jiang, Tengjiao; Han, Qiang; Li, Chunlei
Abstract: Origami metamaterials can control the propagation and energy transmission of elastic waves via the flexible design of microstructure topology, which has great application prospects in the field of structural impact resistance. In this paper, by integrating the Bloch theorem and the local resonance (LR) mechanism, a tunable hybrid origami metamaterial (HOM) is proposed to achieve low-frequency and broad bandgaps (BGs) for realizing wave transmission and impact mitigation. The elastodynamic wave equation of the HOM is established based on the Mindlin plate theory and discretized with the higher-order spectral elements, and band structures of the HOM are obtained through the semi-analytical periodic spectral plate (PSP-SAFE) methods. Effective dynamic properties of the HOM are numerically calculated to explain wave transmission behavior. Interestingly two complete BGs in the low-frequency range are found, and the proposed metamaterial can broaden the low-frequency bandgaps by coupling the polarization BGs and local resonance BGs. The influences of three significant parameters on two complete BGs within the region of interest are then discussed. Furthermore, the wave mitigation capacity of locally resonant HOM is investigated under impact pulses. It is noted that the reaction peak force of the HOM possesses an approximately 25.7% better reduction than that of origami structures with no mass inclusion. Especially when the external excitation frequency is consistent with local-resonance BGs, the transmission rate shows dramatically decrease due to the dramatic dissipation of energy in space. The locally resonant hybrid origami metamaterial shows promising potential for applying low-frequency wave attenuation and impact mitigation. Highlights: A hybrid origami metamaterial is designed based on local resonance mechanism. A semi-analytical spectral plate method is proposed to calculate band structures. The influences of significant parameters on local resonance bandgaps are considered. The impact mitigation performance of hybrid origami metamaterials is discussed.